Fasciola hepatica Diagnosed with Endoscopic Ultrasound and Treated with Endoscopic Retrograde Cholangio Pancreatography: A Case Report - Mustafa Zanyar Akkuzu; Ahmet Yavuz; Berat Ebik; Ümit Karabulut; Ali Üzel; Ferhat Bacaksız (Iranian Journal of Parasitology)
This article discusses Fasciola hepatica infection, a zoonotic parasite that lives in the liver bile ducts. A 31-year-old female patient was diagnosed with symptoms such as nausea, increased liver enzymes, and right upper quadrant pain for about a year. The parasite was detected in the common bile duct by Endoscopic Ultrasound (EUS) and removed by Endoscopic Retrograde Cholangio Pancreatography (ERCP). Treatment was performed with 10 mg/kg triclabendazole. Eosinophilia, abdominal pain, and dietary history are important clues in the diagnosis of infection. Imaging methods, especially EUS, play a critical role in diagnosis. With this method, parasites can be seen as mobile hyperechogenic structures. If untreated, parasites can survive in their hosts for many years, therefore early diagnosis and treatment are important in preventing complications. It is recommended to monitor the eosinophil levels and serological test results of patients after treatment. As a result, EUS is a very valuable diagnostic tool in suspected cases.